2011
DOI: 10.1016/j.bbabio.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the mitochondrial permeability transition

Abstract: The mitochondrial permeability transition is an increase of permeability of the inner mitochondrial membrane to ions and solutes with an exclusion size of about 1500Da. It is generally accepted that the permeability transition is due to opening of a high-conductance channel, the permeability transition pore. Although the molecular nature of the permeability transition pore remains undefined, a great deal is known about its regulation and role in pathophysiology. This review specifically covers the characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 128 publications
4
63
0
1
Order By: Relevance
“…There are two explanations for this increase in ROS: 1) the photosensitizer may transfer its energy to form highly reactive 1 O 2 when oxygen is present in the environment as previous studies have reported that 1 O 2 may be one of the mediators of the imbalance in intracellular ROS; 29 and 2) the activated photosensitizer may react directly with organic substrates or via electron or hydrogen transfer to yield free radicals. 28 Our results indicated that the ROS inhibitor, NAC, and the 1 O 2 inhibitor, NaN 3 , significantly blocked intracellular ROS increases ( Figure 4A). Furthermore, the scavenger of the hydroxyl radical, mannitol, also facilitated cell viability decreases following PDT.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…There are two explanations for this increase in ROS: 1) the photosensitizer may transfer its energy to form highly reactive 1 O 2 when oxygen is present in the environment as previous studies have reported that 1 O 2 may be one of the mediators of the imbalance in intracellular ROS; 29 and 2) the activated photosensitizer may react directly with organic substrates or via electron or hydrogen transfer to yield free radicals. 28 Our results indicated that the ROS inhibitor, NAC, and the 1 O 2 inhibitor, NaN 3 , significantly blocked intracellular ROS increases ( Figure 4A). Furthermore, the scavenger of the hydroxyl radical, mannitol, also facilitated cell viability decreases following PDT.…”
mentioning
confidence: 71%
“…28 Evidence has suggested that oxidative stress is a potential common mediator of apoptosis. Therefore, the generation of ROS, particularly 1 O 2 molecules following PDT treatment, plays a key role in regulating the efficiency of photosensitization.…”
mentioning
confidence: 99%
“…5B). We also tested whether TSPO contributes to the inducing effects of Cu(OP) 2 , which acts at IMM site(s) facing the OMM, and PhAsO, which acts at a matrix site (57). It can be seen that both inducers caused mitochondrial permeabilization irrespective of the presence (Fig.…”
Section: Tspo Does Not Play a Role In The Regulation Of Pt-mentioning
confidence: 99%
“…At one site, low doses of light inactivate the PTP through modification of critical histidines, which in turn causes a drop in the reactivity of matrix-exposed cysteines, probably on the core components of the PTP, stabilizing the pore in a closed conformation (65). In contrast, at the second site, higher light doses coincide with modification of IMS-exposed cysteines that promote PTP activation (55,57). This activation requires the presence of the OMM, given that mitoplasts are refractory to PT activation even after prolonged irradiation (56).…”
Section: Tspo Does Not Play a Role In The Regulation Of Pt-mentioning
confidence: 99%
“…High levels of calcium influx and generation of reactive oxygen species (ROS) have been associated with this form of cell death (Halestrap and Pasdois 2009). These trigger cell death, in part, by causing a mitochondrial permeability transition (mPT), in which the mitochondrial inner membrane becomes permeable to small solutes (Ricchelli et al 2011). This results in a rapid dissipation of the transmembrane potential, followed by matrix swelling and often rupture of the mitochondrial outer membrane.…”
Section: Other Necrosis Signaling Pathwaysmentioning
confidence: 99%